Revisiting an arid LGM using fluvial archives: a luminescence chronology for palaeochannels of the Murrumbidgee River, south‐eastern Australia. (24th August 2018) - Mueller, Daniela; Jacobs, Zenobia; Cohen, Tim J.; Price, David M.; Reinfelds, Ivars V.; Shulmeister, James
ABSTRACT: The Riverine Plain in south‐eastern Australia contains numerous palaeochannels that are much larger than the present rivers and provide evidence about past hydrological conditions. Previous research suggested optima in fluvial activity both before and after the peak of the Last Glacial Maximum (LGM; 21 ± 3 ka), and, in some cases, throughout the LGM. In this study, we revisit palaeochannel remnants of the Gum Creek and Yanco palaeochannel systems along the Murrumbidgee River, which drains the high‐elevation catchments of the Australian Alps in south‐eastern Australia. We date fluvial and aeolian sediments using single‐grain optically stimulated luminescence (OSL) and apply thermoluminescence (TL) dating to a subset of samples. We compare the OSL ages to new and previously published TL ages and investigate reasons for age discrepancies between these methods, possible effects of partial bleaching and other factors that may affect luminescence ages. We propose a new OSL‐based chronology for the Gum Creek and Yanco palaeochannel systems and assign periods of enhanced fluvial activity for the Tombullen and Yanco phases to 41–29 and 29–18 ka, respectively. Importantly, we infer that conditions of increased sediment and water discharge persisted for the Murrumbidgee River at the time of the LGM.